Surfaces environmental monitoring of SARS-CoV-2: Loop mediated isothermal amplification (LAMP) and droplet digital PCR (ddPCR) in comparison with standard Reverse-Transcription quantitative polymerase chain reaction (RT-qPCR) techniques - Simona Spiteri; Irene Salamon; Luna Girolamini; Maria Rosaria Pascale; Federica Marino; Carlo Derelitto; Laura Caligaris; Simone Paghera; Manuela Ferracin; Sandra Cristino (PLoS ONE, 2025)
The persistence of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) on substrates, and the impact of fomites on Coronavirus Disease 19 (COVID-19) transmission, is until now, widely discussed. Consequently, further investigations are required for a correct risk assessment in high-risk facilities such as hospitals, healthcare facilities (HCFs), and long-term care facilities (LTCFs). Therefore, appropriate surveillance and disinfection programs represent the best approach to guarantee the safety of these communities. This study proposes an environmental SARS-CoV-2 surfaces routine monitoring approach in HCF and communities’ settings, to provide rapid and effective evaluation of surface hygienic conditions and the effectiveness of applied sanitization measures. Surfaces samples (n = 118) were collected using the SRK® kit (Copan Italia) from 2020 to 2023. Three molecular techniques were compared: Reverse Transcription Loop mediated isothermal AMPlification (RT-LAMP, Enbiotech), Reverse-Transcription quantitative polymerase chain reaction (RT-qPCR) (RT-qPCR, Seegene) and droplet digital PCR (ddPCR, Bio-Rad). For ddPCR, two RNA extraction methods were compared: TRIzol LS (Invitrogen) versus QIAmp Viral Mini kit (QIAGEN), showing how the latter is more suitable for surfaces. Regarding the quantitative ddPCR results, the ROC analysis allowed to reduce the manufacturer cut-off for droplets number (from 3 to 1) for the positive samples. Moreover, a new cut-off for the viral RNA copies’ number/μL for each target (N1 and N2) on environmental monitoring was fixed at 2,82. The results obtained using the QIAmp kit, suggested that the N2 target is more stable in the environment and could be most suitable for the virus environmental detection. The percentage of positive samples was similar among the techniques (26% for RT-LAMP, 36% for ddPCR and 23% for RT-qPCR). Using RT-qPCR as reference method, a sensitivity (SE) of 30% for RT-LAMP and 41% for ddPCR was observed. By contrast, specificity (SP) was higher for RT-LAMP (75%) respect to ddPCR (66%). Comparing the faster RT-LAMP with the sensitive ddPCR the 26% and 74% of SE and SP for RT-LAMP, were reported. The low sensitivity for RT-LAMP and ddPCR could be explained with the use of clinical rather than environmental kits, other than the changing in the virus prevalence during the sampling campaign. Although the RT-LAMP requires improvements in term of SE and SP, this research presents an innovative environmental monitoring and prevention method for SARS-CoV-2, that could be extended to other pathogens that are under environmental surveillance.